De la « déportation-abandon » à la réintégration des « ex-koulaks » : les modulations de la répression à l’égard des paysans soviétiques (1930-1948) - Hélène Mondon (Les Cahiers de Framespa)
« Dekulakization » represents the largest operation of all Stalinian mass deportations. In 1930 and 1931, more than one million eight hundred thousand peasants were sent into internal exile, becoming Stalin’s first « special settlers ».In 1930, the Soviet Northern territory was chosen to be the laboratory of this repressive and social experimentation on human beings that obliged thousands of peasant families to extract the natural resources of these frozen hinterlands. They had to remain durably in the so-called « special villages » built for their rehabilitation.This paper, based on archival materials combined with survivors’ stories, throws new light on the fate of peasant families in the North, their survival strategies when facing the most horrific first years of repression, as well as their strategies of adaptation and rehabilitation within society from the second half of the 1930s on. This research reveals the changes that occurred in the « special settlements » during the war and charts the process of the deportees’ liberation after eighteen years of exile, marking the end of the longest deportation initiated –and eventually defused– by Stalin.